2022
DOI: 10.3390/ijerph192214886
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Pregnancy: Knowledge about the Vaccine and the Effect of the Virus. Reliability and Results of the MAMA-19 Questionnaire

Abstract: Background: Fear or mistrust of the vaccine and concern for the well-being of their unborn infants are the main reasons for COVID-19 vaccine hesitancy in pregnant women. The aim of this work was to validate a questionnaire on knowledge about COVID-19 vaccination during pregnancy and to examine the sources of information in a group of new mothers, as well as their effectiveness and intelligibility. Methods: A literature review was carried out to develop a questionnaire of forty-five questions, divided into six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…Our study also highlights that women with comorbidities, despite being more vulnerable to disease, have a lower vaccination rate, similar to the data obtained by Snajider et al [24]. We also evaluated the role of information sources related to active immunization and found that HCWs played a large part in the empowerment and adherence of pregnant women with higher vaccination coverage, as indicated in other studies [27].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study also highlights that women with comorbidities, despite being more vulnerable to disease, have a lower vaccination rate, similar to the data obtained by Snajider et al [24]. We also evaluated the role of information sources related to active immunization and found that HCWs played a large part in the empowerment and adherence of pregnant women with higher vaccination coverage, as indicated in other studies [27].…”
Section: Discussionsupporting
confidence: 89%
“…Our results show a high vaccination rate, reaching 90%, most likely derived from the distribution of the sample. In fact, we found that educational degree and age had a high impact on the acceptance of vaccination, as indicated by Del Giudice et al [23], and similar to another study, our sample was predominantly composed of people with higher educational attainment compared to those with medium-low instruction levels [24].…”
Section: Discussionsupporting
confidence: 87%
“…In a Spanish study conducted among 302 pregnant women and 309 healthcare workers investigating factors acting as major decision makers for receiving a vaccination, a recommendation from healthcare workers was the most pivotal influence for pregnant women, with 73% naming it as an influencing factor [ 33 ]. An Italian survey revealed that a physician’s recommendation to be vaccinated against COVID-19 is the most important factor in maternal decision making, regardless of geographic, social, or educational context [ 34 ]. Similarly, in the previously mentioned French survey performed in Spring 2021, pregnant women who received information from a healthcare provider (HCP) were more likely to accept vaccination [ 32 ].…”
Section: Discussionmentioning
confidence: 99%